Dravidar Iyakkam Advocated by Thanthai Periyar Contains Nuances of Karl Marx's Communist Manifesto (Global Journal of Human-Social Science, 2023)
Right to live, equity and social justice are watch words that determine quality of life in a society. But Tamil Society witnessed harassment by handful of men who branding themselves as the higher social hierarchy dominated the rest for decades resulting great social inequality. Devaneya Pavanar in his forward to his book entitled "Tamilar Varalaru" published by Poompuhar Pathippagam, states that "there is a concept revolving in the country for the past three thousand years that Brahmins are inherited from God, sanscrit is the mother of all languages and it is the language of Gods and Tamil had lost its rationality; self-respet and self-confidence. Pavanar also states that though British Rule developed the country; the Justice Party uplifted the coman man; the research in language unravels the truth; Periyar however cautioned Tamils; however Maraimalai Adigal taught the Tamils for their emancipation they remain the same. After the Britishers left India the minority Muslims attain separate nation but not the Tamils.